ATP and chlorophyll α of microplankton in the Bransfield Strait during the early autumn 2002 - A. A. Sysoyev (Ukrainian Antarctic Journal, 2004)
The study of ATP and chlorophyll α as indices of metabolic active biomass and autotrophic component of microplankton has shown dissimilar distribution character of explored parameters. Their differences reached the scope of one order. It was shown that high variability of the biochemical parameters depended clearly on hydrological and topographical features of researched areas. High concentrations corresponding to eutrophic criterions were noted in northern and western parts of polygon, where influences of the Drake Strait and Bellingshausen Sea were significant. Low values, which were similar to oligotrophic means, recorded in the southern part of polygon, which affected by water of the Weddell Sea. According to autotrophic index the parity biomasses of auto- and heterotrophic microplankton were marked in a medial part of a polygon, while the peripheral sites, in particular in north-west, were characterized by the autotrophic majorant. The size structure analysis showed prevalence of biomass of large fractions in the euphotic layer and tendency to the increase of share of small size microplankton with deepening on peripheral areas of polygon.